2006
DOI: 10.1099/vir.0.81844-0
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus NS4B interacts with NS3 and dissociates it from single-stranded RNA

Abstract: Dengue virus, a member of the family Flaviviridae of positive-strand RNA viruses, has seven non-structural proteins: NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5. Except for enzymic activities contained within NS3 and NS5, the roles of the other proteins in virus replication and pathogenesis are not well defined. In this study, a physical interaction between NS4B and the helicase domain of NS3 was identified by using a yeast two-hybrid assay. This interaction was further confirmed by biochemical pull-down and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
166
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(177 citation statements)
references
References 52 publications
8
166
0
3
Order By: Relevance
“…Although evidence suggests that the small, hydrophobic NS4A protein (approx. 16 kDa) is required for viral replication, and that NS4A may serve as a central 'organizer' of the replication complex of flaviviruses (Lindenbach & Rice, 1999;Paredes & Blight, 2008;Umareddy et al, 2006), its precise functional role is not characterized sufficiently. NS4A associates with membranes via four internal hydrophobic regions.…”
mentioning
confidence: 99%
“…Although evidence suggests that the small, hydrophobic NS4A protein (approx. 16 kDa) is required for viral replication, and that NS4A may serve as a central 'organizer' of the replication complex of flaviviruses (Lindenbach & Rice, 1999;Paredes & Blight, 2008;Umareddy et al, 2006), its precise functional role is not characterized sufficiently. NS4A associates with membranes via four internal hydrophobic regions.…”
mentioning
confidence: 99%
“…Although the functions of NS2A, NS4A, and NS4B have not yet been fully elucidated, several studies suggest that they may anchor the viral replicase proteins to cellular membranes, 52 assist in virion assembly, 53,54 and lead to inhibition of the interferon a/β response. [55][56][57][58] It has been reported that NS4A may play a role in induction of membrane alterations, assumed to serve as a scaffold for the formation of the viral replicase complex, 59 and the interaction between NS1 and NS4A, which is critical for viral RNA replication. 59,60 Mutations in the NS2A protein that diminish its ability to inhibit the host interferon response could contribute to the non-predominant status of genotype III viruses.…”
mentioning
confidence: 99%
“…Recently NS4A was proven to act as a cofactor for NS3 helicase allowing the helicase to sustain the unwinding rate of the viral RNA under conditions of ATP deficiency [41]. NS4B colocalizes with viral replication complexes and proved to dissociate NS3 from single-stranded RNA, thereby enabling it to bind to a new dsRNA duplex, consequently enhancing the helicase activity and modulating viral replication [42,43]. In addition, NS4A and NS4B, along with NS2A, as has already been referred, and NS5 proteins appear to inhibit the interferon-/ response of the host [44][45][46].…”
Section: Introductionmentioning
confidence: 99%